Inter Akt. - Hesselhund, Birgit; Kunstnernes Hus, Arhus; Arhus Kunstforening af 1847, Arhus (Arhus : Prisma, 1992)
Blaabjerg, Lise ; Bosch, Bertine ; Frank, Niels ; Have, Finn ; Heinermann, Claudia ; Meinen, Bert ; Meinen, Merel Eva ; Munk, Hanne ; Piene, Hans ; Raemaekers, Philomeen ; Rasmussen, Inge ; Sylvest, Niels ; Tast, Steffen ; Van Eck, Pieter ; Vohnsen, Esther ; Wesker, Hans ; Rasmussen, Steen
Losse bladzijden per kunstenaar
Kunsternes Hus, Arhus ; Arhus Kunstforening af 1847, Arhus, 1992
kunstcatalogus